PENGARUH PENERAPAN MODEL ORGANIZING, REFLECTING TERHADAP KEMAMPUAN MENULIS TEKS BERITA PADA SISWA - SISWI SLTP - DORTYA . (JURNAL ILMIAH MAKSITEK, 2021)
Influence is the force that exists or arises from a person, (person, thing) that contributes to the organization, beliefs, oractions of a person. "Organizing, Reflecting, is learning that has two aspects, namely: a) Organizing is an activity to organizeideas to understand the material, b) Reflecting is an activity to rethink, explore, and dig up information that has beenobtained". The data analysis techniques used are the Normality test using the F test, the Homogeneity test and theHypothesis test using the "t" test. The hypothesis in this study was tested with a "t" test at a significant level ∝ = 0.05. Fromthe calculation data thitung > ttabel (6,667>2,000). Thus the null hypothesis that Ho was rejected and Ha accepted. Basedon the above understanding can be concluded that Ability is a skill, talent or skill that a person has in doing something. Theskill that is fulfilled in this case is the proficiency in writing text.